Development of RT-qPCR assays for the specific identification of two major genotypes of avian infectious bronchitis virus - Marandino, Ana (2016)
Infectious bronchitis virus (Gammacoronavirus, Coronaviridae) is a genetically variable RNA virus (27.6kb) that causes one of the most persistent respiratory disease in poultry. The virus is classified in genotypes with different epidemiological relevance and clinical implications. The present study reports the development and validation of specific RT-qPCR assays for the detection of two major IBV genotypes: South America I (SAI) and Asia/South America II (A/SAII). The SAI genotype is an exclusive and widespread South American lineage while the A/SAII genotype is distributed in Asia, Europe and South America. Both identification assays employ TaqMan probes that hybridize with unique sequences in the spike glycoprotein gene. The assays successfully detected all the assessed strains belonging to both genotypes, showing high specificity and absence of cross-reactivity. Using serial dilutions of in vitro-transcribed RNA we obtained acceptable determination coefficients, PCR efficiencies and relatively small intra- and inter-assay variability. The assays demonstrated a wide dynamic range between 10(1)-10(7) and 10(2)-10(7) RNA copies/reaction for SAI and A/SAII strains, respectively. The possibility to characterize a large number of samples in a rapid, sensitive and reproducible way makes these techniques suitable tools for routine testing, IBV control, and epidemiological research in poultry